The Design of Klettern Media Promotion - Hamdani, Nurvivi; Triani, Ananda Risya (VCD, 2017)
The use of the Internet as a promotional and business media grows higher. Internet makes it easy for businesses to market their products or services. A brand named Klettern that sell outdoor gear products, market their products through online promotional media such as Facebook and Instagram. But, marketing is done through the media is not able to attract these consumers, because not every community or target market used the social media. Therefore, optimizing the strategy of content is very important for marketing the product. In marketing, it takes a strategy for the products offered to align with the needs of consumers. One of the route that can be used is the inbound marketing technique that comprised of content marketing and social media participation. In this study, the author conducted several data collection methods, such as literature studies, observation, interviews, questionnaire, and documentation. Through the research, it is expected that Klettern brand can devise a grand plan to promote and expand their market nationwide and overseas.